Upaya Meningkatkan Kemampuan Mengingat Huruf Pada Anak Usia 4-5 Tahun Melalui Metode Bernyanyi di PAUD At-Taufiq - Hindun, Siti; Zultiar, Indra; Munajat, Asep (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to improve letter recall abilities in children aged 4-5 years through the singing method at PAUD AT-TAUFIQ. Using Classroom Action Research (CAR) method in two cycles, this study involved 19 children from Group A. The results showed significant improvement, where the "Not Developed" (ND) category, initially 21%, dropped to 0% in Cycle II. The "Beginning to Develop" (BTD) category decreased from 37% to 21%, and the "Developing as Expected" (DAE) category decreased from 37% to 21%. Meanwhile, the "Very Well Developed" (VWLD) category increased from 5% to 69%. These findings prove that the singing method is effective in enhancing letter recall abilities, making it recommended as a learning strategy in PAUD.